PENGARUH RASIO UDARA BAHAN BAKAR SOLAR DAN GAS TERHADAP KUALITAS SATURATED STEAM PADA SISTEM TWO DRUM WATER TUBE BOILER - Rusnadi, Irawan; ., Fatria; Zikri, Ahmad; Lestari, Sutini Pujiastuti; Alvino, Raudi; Jaya, Julian Indra (KINETIKA, 2020)
A boiler is an equipment used to produce steam for various purposes. In this case, the boiler used also often has problems that cause less than optimal steam results. The obstacle that occurs is usually the ratio of air to fuel which causes the combustion results to be not optimal and imperfect so that it has an impact on the production and quality of the steam produced. One of the parameters of the steam produced is temperature and pressure. Both will relate to the enthalpy of steam as a measure to determine the value of the energy contained in the steam. Therefore, this research focuses on determining the most optimal and precise ratio of air to diesel fuel and gas so that maximum combustion results are obtained. The air-to-fuel ratio which is the variable for diesels are 123.67, 128.33, 133.00, 137.67, 142.33 and for gas are 29.16, 29.44, 29.71, 29.99 and 30.26. In the resulting data, the fourth of the air fuel ratio of diesel fuel which is more optimal and precise, which is 137.67 and 29.99 for gas with the resulting value of temperature is 151oC, pressure is 5 bar and the value of the saturated steam quality is 0.7993 â‰ˆ 0.8.